MICROPLASTIC–MICROBIOME INTERACTIONS IN MARINE AND FRESHWATER ECOSYSTEMS (Journal of Medical & Health Sciences Review, 2025)
Background: Microplastic contamination is becoming a major worldwide environmental hazard, which influences the aquatic biodiversity, as well as the community dynamics of microorganisms in marine and freshwater environments. The microscopic plastic particles are artificial sources of microbial colonization that create separate communities in the form of a plastisphere, which affect nutrient cycling, pathogen dispersal, and ecosystem wellbeing. Although the interest has increased, there is still a lack of knowledge and awareness among the population as to the interaction between microplastics and the microbiome. This research was conducted to assess the degree of awareness, perception, and understanding of these interactions in the various demographic groups and to statistically confirm the relationships between the critical perception variables.Methods: A cross-sectional quantitative design was adopted by use of a structured Likert scale questionnaire with 16 questions that were distributed under the four different domains: awareness, ecological impact, health and food chain concerns, and mitigation perception. Three hundred answers were obtained from respondents representing different parts of Pakistan. The analyses involved Normality analysis (Shapiro-Wilk), Reliability (Cronbach's Alpha), Validity (KMO and Bartlett test), Independent Samples t-test, one-way ANOVA, Kruskal-Wallis, Chi-square analysis, Pearson correlation, and Multiple regression analysis. All the analyses were conducted in SPSS and Python-based statistical modeling.Results: The findings established that all the variables were normally distributed (p > 0.05) and consistent internally with a total Cronbach's Alpha of 0.911, which is excellent. Construct validity was determined by the value of KMO (0.846) and the significance of the Bartlett Test (x 2 = 2643.217, p < 0.001). The difference between the groups was statistically significant in terms of gender (t = 2.684, p = 0.008), education (F = 4.327, p = 0.014), region (H = 10.562, p = 0.032), and gender x education correlation (H 2 = 18.246, p = 0.021). The correlation table showed high positive relationships between all the variables of perception (r = 0.64-0.81). Regression analysis also showed that the overall perception was significantly and positively (β = 0.1380.312) contributed by all predictors and accounted for 68.2 percent variance (R 2 = 0.682).Conclusion: The results reveal an elevated degree of awareness and a positive, strong correlation between ecological knowledge and health-related issues and mitigation plans on the interaction of microplastics and microbiomes. These perceptions are greatly influenced by education, gender, and regional background, motivating the need to adopt specific environmental education and awareness programmes. The paper summarizes that sustainable strategies of water management and pollution control would be impossible without improving the general literacy of the population regarding the mechanisms of interaction between microplastics and microbiomes. The questionnaire constructed in the course of the study and validated and reliable, can be applied as a useful instrument in future ecological perception studies and policy-making.